Development of food for special dietary uses of diabetes based on oyster mushroom and brown rice - Inggita Kusumastuty; Etik Sulistyowati; Dian Handayani; Fajar Ari Nugroho; Anggun Rindang Cempaka; Agustin Rustiani; Alfina Putri Rakhmadiyah; Muhamad Zulkifli; Hana Raniza Jasmine; Gemma Karnika Prakasita; Firza Zahra Amanda; Ajeng Rifana Putri (PAGEPress Publications, 2024)
Diabetes patients often struggle to meet their energy requirements, prompting the suggestion of utilizing Food for Special Dietary Uses (FSDU). Previous research has shown the efficacy of oyster mushrooms' B-glucan in controlling hyperglycemia and insulin resistance. Brown rice, high in magnesium and fiber with a low glycemic index, is known to lower blood glucose levels. Utilizing both ingredients in FSDU may provide products with recommended energy value, nutrient ingredients, and glycemic index. This study aimed to measure the energy, protein, fat, carbohydrate, fiber, glucose, and glycemic index of four mixed formulations of oyster mushrooms and brown rice, along with a control. The study used a true experimental design with a completely randomized research design. The formulations included: P1=9% mixture of moringa and fish flour, P2=10% mixture of carrot and fish flour, F3=11% mixture of moringa and tempeh flour, and F4=12% tempeh flour.  The total energy was measured using various methods: adiabatic oxygen bomb calorimeter for energy, Kjeldahl for protein, Soxhlet for fat, by-difference for carbohydrates, AOAC enzymatic-gravimetric for total dietary fiber, anthrone for total sugar, and blood glucose tests at 0, 15, 30, 45, 60, 90, and 120 minutes post-test-food ingestion for glycemic index measurements. Statistical analysis was performed using the One-Way ANOVA and Kruskal-Wallis tests. The research results indicate significant differences in energy, protein, fat, carbohydrates, total sugar, and fiber values among groups (p<0.01). The lowest glycemic index was found in P4 (44.32, medium category). Further analysis indicated that P4 had higher total energy and fat, but lower carbohydrates, total sugar, and glycemic index. According to the Multiple Attribute Zeleny Method, the P4 formula was the best formula for all parameters. The most effective formula, containing brown rice, oyster mushrooms, and tempeh flour (P4), could be a beneficial option for improving the health of individuals with diabetes in the community.